By-Laws, Rules and Regulations : 2009. (By Laws, Rules and Regulations; Sixty-First Issue, May 2009, 2009)
This paper presents the By-Laws rules and regulations provide operating rules, procedures, regulations, and interpretation as are necessary and desirable to carry out the purposes and powers contained in the Articles. If any provision in the Rules and Regulations is found to be in conflict with any provision in the Articles or in the By-Laws, the Articles and By-Laws shall prevail and an appropriate amendment shall be made to these Rules and Regulations. Except in special circumstances the Chairman shall notify Executive Directors of new items on the agenda at least two full business days before their consideration in meetings. The working language of the IMF shall be English. The discussion, documents, and reports of meetings shall ordinarily be in English. When a country applies for membership in the IMF, the application shall be placed promptly before the Executive Board, and a reasonable time shall be allowed for discussion and preliminary investigation by the Executive Board before a decision is reached to proceed with the formal investigation.